A qualitative study of tobacco use in eight economically disadvantaged Dominican Republic communities. (December 2017) - Chin, Nancy; Dozier, Ann; Quinones, Zahira; Diaz, Sergio; Weber, Emily; Almonte, Hector; Bautista, Arisleyda; Raman, Kiran; McIntosh, Scott; Ossip, Deborah
Understanding social conditions prior to intervention design can enhance tobacco control interventions. This paper describes formative research conducted in 2010 about tobacco use in eight economically disadvantaged Dominican Republic communities, four of which participated in a previous intervention study (2003–2008). A combined US-Dominican team used a rapid assessment process to collect qualitative social and cultural data on tobacco use, knowledge and attitudes; plus observations about social and policy factors, such as exposure to secondhand smoke (SHS), tobacco regulations, pregnancy, health care provider (HCP) practices and sustainability of the 2003–2008 intervention. This assessment found that tobacco use varied by age. While all ages typically used cigarettes, older adults used relatively more unprocessed tobacco, which is seen as less harmful and less addictive. Middle-aged smokers typically used commercial cigarettes, which are viewed as dangerous, addictive, expensive and offensive. Young adults reported avoiding smoking, but using relatively more smokeless tobacco. Smoking during pregnancy has reportedly decreased. SHS was viewed as harmful, although smoke-free homes were uncommon. HCPs discussed tobacco issues mostly for patients with tobacco-related conditions. Sustainability of the 2003–2008 intervention appeared to be linked to active Community Technology Centers with strong leadership, and community social capital. This information could be used to design better targeted interventions in these communities.